Serum concentrations of cartilage oligomeric matrix protein and bone sialoprotein in hip osteoarthritis: A one year prospective study. Issue 9 (1st September 1998) - Conrozier, Thierry; Saxne, Tore; Fan, Charles Shan Sei; Mathieu, Pierre; Tron, Anne-Marie; Heinegård, Dick; Vignon, Eric
Abstract : OBJECTIVE: To evaluate serum concentations of cartilage oligomeric matrix protein (COMP) and bone sialoprotein (BSP) as predictors of disease progression in hip osteoarthrtitis (OA). METHODS: Forty eight consecutive patients, referred to hospital for symptomatic hip OA, (ACR criteria) were monitored in a one year prospective trial with radiographs and serum samples. The radiographs were graded for joint space narrowing, osteophytes, and sclerosis and the joint space width was measured by a digitised image analyser. Serum COMP and BSP were quantified by immunoassays. RESULTS: The COMP concentrations at baseline correlated with the joint space width at entry and with its yearly mean narrowing ( r = 0.38, p = 0.002) but not with joint space narrowing grade progression. The concentrations were higher in patients with bilateral hip OA (p = 0.03). The serum BSP concentrations at baseline were unrelated to OA progression but correlated inversely to the osteophyte grade ( r = −0.36, p = 0.004) and sclerosis grade ( r = −0.42, p = 0.0004). CONCLUSION: Serum COMP seems to be a surrogate marker of OA and may be of interest for the detection of patients at risk of rapidly progressing disease in hip OA. Serum BSP changes seem to reflect alterations in the subchondral bone turnover in hip OA. Measurement of joint space width using a digitised image analyser is a sensitive way of assessing OA progression that facilitates evaluation of tissue markers in relation to anatomical changes in the joint.